Correlation of Bullying with Anxiety among Teenagers - Elis Roslianti; Susi Susilawati; Ima Sukmawati (Inspirasi Foundation, 2020)
Introduction: Bullying is an aggressive behavior of someone or a group of people which attack, insult and ostracize the helpless people repeatedly. Bullying is well known as a social problem that is often found especially in teenager. The impact that usually appear as the effect of bullying behavior is anxiety. Anxiety is a 'not fun' emotional condition that can affect his perception about something and the physical condition from the individual that can be happened in any situations. Objective: the objectives of this research is to know the relationship between bullying and the teenager anxiety level Method: method in this research was a quantitative research with cross-sectional approach. Sample was taken by using total sampling, as many as 32 respondents. This research instrument used HARS questionnaire by sharing check list sheet to the respondents which was consisted of 20 questions. Result: the result in of research showed teenager in little anxiety category as much (3,1%), moderate anxiety (34,4%), severe anxiety (12,5%) very severe anxiety (50,0%) verbal bullying category (50%), nonverbal bullying (50%). Conclusion: there is a significant between bullying occurrence in teenager and the very severe level of anxiety because p-value < a (0,00 < 0,05).